Bible and transformation: the promise of intercultural Bible reading - Wit, Hans de; Dyk, J. W. (Semeia studies, 2015)
"This book offers the results of research within a new area of discipline--empirical hermeneutics in intercultural perspective. Ordinary readers from more than twenty-five countries in interaction with a distant partner group engage the stories of the rape of biblical accounts. Interpretations from the homeless in Amsterdam, to Indonesia, from African Xhosa readers to Norway, to Madagascar, American youths, Germany, Czech Republic, Colombia, and Haitian refugees in the Dominican Republic offer a (road)map of the sometimes delightful and inspiring, sometimes rough and rocky road to inclusive and transformative Bible reading"--